Workplace environmental factors and stress management among academic staff of federal universities in south- west, Nigeria (2017)
Most academic staff have been found to be experiencing high level of stress, arising from long working hours, increased job demands. lack of control over work-pace and imbalanced work-life relationships. These in turns lead to feelings of worry, anxiety, anger, frustration, depression, high rates of hospitalisation and sudden deaths, and low performance. Previous studies have attempted to address this problem using mostly psychological and medical interventions with little emphasis on the degree of assistance available within the social and institutional networks in the university work environment. The study, therefore, examined the combined influence of workplace environmental factors (work load. role ambiguity/conflict and class size), social (career advice. connectedness and provision of feedbacks) and institutional (research assistance, promotion, collegiality. protection, friendship and opportunity) supports on the management of stress among academic staff in federal universities in the South-west. Nigeria. This study adopted the descriptive survey design. Four of the oldest federal universities in the South-west were purposively selected. Two research hypotheses were tested for the study al 0.05 level of significance. Data were analysed using Pearson Product Moment Correlation Coefficient and. Multiple Regression. Effective social support System coupled with opportunities for promotion and research assistance as well as availability of flexible work load positively determined the management of stress among academic staff in federal universities in the South-west. Nigeria. There is the need to improve upon thè social supports while effective institutional supports should be provided to enhance the stress management System among thè academic staff. In addition conducive and flexible work environment should be ensured